Hypothalamus-pituitary-adrenal and gut-brain axes in biological interaction pathway of the depression - Bertollo, Amanda Gollo; Santos, Camila Ferreira; Bagatini, Margarete Dulce; Ignácio, Zuleide Maria (Frontiers in Neuroscience, 2025)
The hypothalamus-pituitary-adrenal (HPA) and gut-brain axes are vital biological pathways in depression. The HPA axis regulates the body's stress response, and chronic stress can lead to overactivation of the HPA axis, resulting in elevated cortisol levels that contribute to neuronal damage, particularly in regions such as the hippocampus and prefrontal cortex, both of which are involved in mood regulation and mental disorders. In parallel, the gut-brain axis, a bidirectional communication network between the gut microbiota and the central nervous system, influences emotional and cognitive functions. Imbalances in gut microbiota can affect the HPA axis, promoting inflammation and increasing gut permeability. This allows endotoxins to enter the bloodstream, contributing to neuroinflammation and altering neurotransmitter production, including serotonin. Since the majority of serotonin is produced in the gut, disruptions in this pathway may be linked to depressive symptoms. This review explores the interplay between the HPA axis and the gut-brain axis in the context of depression.